Business ethics and corporate social responsibility - Maximiano, Jose Mario B. (Pasig City, Philippines : Anvil Publications, 2007)
This books comes at just the right time. Now, more than ever, we need leasders, not only in our public offices, but also in business sector with a heart for people whom they consider as the greaest resource in any industry.
Part one : Business ethics and corporate social responsibility -- Part two : Moral theories and principles -- Part three : Applications to the various stakeholders of business.
Includes bibliographical references.
Keywords: BUSINESS ETHICS -- PHILIPPINES